The Characteristics of Domestic Wastewater from Office Buildings in Bandung, West Java, Indonesia - Vandith VA; Ahmad Soleh Setiyawan; Prayatni Soewondo; Dyah Wulandari Putri (Universitas Trisakti, 2018)
Domestic wastewater generated from various types of buildings has been recognized to be different to some extent. This research aimed to know the quality, quantity, fluctuation of quality, and fluctuation of quantity of domestic wastewater discharged from office buildings. The composite samples were taken from two office buildings. The black water and gray water were taken from Building A with number of people 53 persons, and the mixed wastewater was taken both from Building A and Building B with number of people 900 persons. The fluctuation and quantity of wastewater were measured every hour from 7 am until 4 pm during the working time. The results showed that the quality of wastewater from office building contained 176 to 238 mg/L COD, 73.06 to 106.51 mg/L TN, and 3.66 to 7.70 mg/L TP with the average of C:N:P ratio was 100:42:2.56. Quantity of wastewater discharged from office buildings were from 39.61 to 49.93 liter/person/day. COD concentration changed significantly during the working time with mean ± standard (252.5±89). The quantity of wastewater varied over time and the peak discharge for black water and gray water were 2.85 litter/person/hour and 3.74 liter/person/hour, which occurred during the beginning of working time and the praying time of muslim Indonesian culture. It suggests that the domestic wastewater from office buildings has specific characteristics and it contains high concentration of nutrient that is required appropriate advanced technology for treating this kind of wastewater.